TALIF at H− ion sources for the determination of the density and EDF of atomic hydrogen. (10th March 2023) - Merk, F; Wimmer, C; Briefi, S; Fantz, U
Abstract: The production of H − ions in negative ion sources relevant for particle accelerator facilities and neutral beam injection systems is based predominantly on the surface conversion of H atoms at a low work function surface covered with caesium (the plasma grid (PG)). Therefore, the H atom density n H and energy distribution function (EDF) close to the PG determine the amount of surface produced H − ions. As a direct method for the density and EDF determination, two-photon absorption laser induced fluorescence (TALIF) on H atoms was implemented at the ion source of the teststand BATMAN Upgrade (BUG) being the first time that this was accomplished at an H − ion source. Several challenges had to be overcome concerning the application of the diagnostic at the complex facility and the evaluation of the fluorescence signals against a bright H α background. The observed line profiles suggest a Maxwellian EDF with an H atom temperature of ( 2000 ± 500 ) K. The presence of highly energetic H atoms (measured by optical emission spectroscopy, (OES)) could not be resolved by the TALIF system due to the insufficient signal-to-noise ratio. Atomic densities were measured for H2 and D2 plasmas for varying ion source parameters at BUG resulting in values between 3 × 10 18 m −3 and 1.1 × 10 19 m −3 for hydrogen. For the operation with deuterium, 30 % higher atomic densities are observed for similar ion source parameters which agree well with the previous results obtained with OES.